Risk Based Improvement Performance Strategy for Operation and Maintenance Activities of River and River Infrastructure (BBWS Ciliwung-Cisadane Authority) - Isni Septima Anindhita (Procedia of Social Sciences and Humanities, 2021)
The Ministry of Public Works and Public Housing (PUPR) has the duty and responsibility to carry out effective and efficient river operation activities and river infrastructure including overcoming floods during the rainy season, but these activities are deemed necessary for improvement in planning procedures. To realize this goal, it is necessary to manage risks that can reduce river performance and river infrastructure as flood control. With risk management in this activity, it is possible to apply the sequence of risks that occur which are then used as recommendations for action (risk response) and risk-based development strategies to improve river performance and river infrastructure to control floods through operation and maintenance activities to build a functional and sustainable system. Suitable for long-term planning and short-term maintenance needs.